Is tuberculosis crossing borders at the Eastern boundary of the European Union? - van der Werf, Marieke J. (Oxford University Press, 2013)
Background: The Eastern border of the European Union (EU) consists of 10 countries after the expansion of the EU in 2004 and 2007. These 10 countries border to the East to countries with high tuberculosis (TB) notification rates. We analyzed the notification data of Europe to quantify the impact of cross-border TB at the Eastern border of the EU. Methods: We used TB surveillance data of 2010 submitted by 53 European Region countries to the European Centre for Disease Prevention and Control and the World Health Organization Regional Office for Europe. Notified TB cases were stratified by origin of the case (national/foreign). We calculated the contribution of foreign to overall TB notification. Results: In the 10 EU countries located at the EU Eastern border, 618 notified TB cases (1.7% of all notified TB cases) were of foreign origin. Of those 618 TB cases, 173 (28.0%) were from countries bordering the EU to the East. More specifically, 90 (52.0%) were from Russia, 33 (19.1%) from Belarus, 33 (19.1%) from Ukraine, 13 (7.5%) from Moldova and 4 (2.3%) from Turkey. Conclusions: Currently, migrants contribute little to TB notifications in the 10 EU countries at the Eastern border of the EU, but changes in migration patterns may result in an increasing contribution. Therefore, EU countries at the Eastern border of the EU should strive to provide prompt diagnostic services and adequate treatment of migrants.